Reflection on The Implementation of Differentiated Social Studies Learning to Support The Achievement of Islamic Personality Values in The Merdeka Curriculum - Habibah, Nur; Yani, Muhammad Turhan; Sarmini,; Suprijono, Agus (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2024)
This study aims to determine the application of social studies learning carried out in a differentiated manner, the implementation process and its impact on students. The researcher will explore data on whether or not this differentiated learning model will be a solution in developing independent learning in implementing differentiated learning for students of MTs. Wachid Hasyim Surabaya with various student needs. The qualitative method was chosen to obtain in-depth data on the implementation of differentiated learning and its relevance to the merdeka curriculum. Meanwhile, the case study was chosen because it describes the phenomenon of differentiated learning innovation by referring to the school that is the focus of the research. From two sources of Islamic teachings related to muamalah matters. The verses about worship and the verses about social life are one in a hundred. For one verse of worship there are one hundred verses of muamalah. Likewise in the hadith books. Of the twenty volumes of Fath al-Bari: Syarah Sahih Bukhari, only four volumes deal with matters of worship. This shows the importance of the personality values of students taught in differentiated learning. Differentiated learning in social studies subjects applied at MTs. Wachid Hasyim Surabaya has had a positive impact on students and teachers. The application of differentiated learning carried out by social studies teachers uses three stages, namely 1) differentiation of content applied in mapping student interests, 2) differentiation of the process. Researchers see that in implementing differentiation learning, teachers are still confused about the concept of proper process differentiation